Pengaruh Financial Leverage dan Ukuran Perusahaan terhadap Pengungkapan Corporate Social Responsibility pada Perusahaan Manufaktur - Nur Rokhmah, Lutvia; Suyanto, Suyanto; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
Disclosure of corporate social responsibility (CSR) is important for the survival of the company. In CSR, companies must pay attention to the triple bottom line, namely economic, social and environmental. This research uses quantitative data from 91 manufacturing companies on the IDX in 2022. The results of the analysis show that DCR has a significant negative effect on CSR, while SIZE has a positive effect. Financial leverage has a negative effect on CSR disclosure, but is not significant. Companies need to increase CSR transparency and disclosure, especially smaller companies